Parent-Implemented Communication Strategies During Storybook Reading. (December 2019) - Akamoglu, Yusuf; Meadan, Hedda
Children with developmental disabilities (DD) may experience delays in their ability to speak and communicate with their parents, peers, and others. These children often benefit from evidence-based, parent-implemented communication interventions. In the current study, two mothers were trained and coached to use storybook reading techniques and evidence-based naturalistic communication teaching strategies (i.e., modeling, mand-model, and time delay) while reading books with their children with DD. Using a multiple-baseline design across naturalistic teaching strategies, the following three components were examined: (a) mothers' use of book reading techniques, (b) mothers' rate and fidelity in using the three naturalistic teaching strategies, and (c) children's communication outcomes. After training and coaching, the mothers used the modeling, mand-model, and time delay strategies with higher rates and higher fidelity. The children initiated more communicative acts upon their mothers' use of time delay. The mothers reported that the training and coaching helped them implement the strategies and led to improvements in their children's communication skills.